2017
DOI: 10.1017/s136898001700249x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition warnings as front-of-pack labels: influence of design features on healthfulness perception and attentional capture

Abstract: Results from the experiments provide recommendations for the design of warnings to identify products with unfavourable nutrient profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 53 publications
1
53
0
10
Order By: Relevance
“…17 This is similar to the final format of the labels implemented in Chile, with a slight difference in wording, which ended up with the text "High in…" for the warning labels. So far, study methods have focused on either virtual stores or shopping simulations, and no studies have investigated in-store sales.…”
Section: Evidence For Warning Labels To Datementioning
confidence: 84%
See 1 more Smart Citation
“…17 This is similar to the final format of the labels implemented in Chile, with a slight difference in wording, which ended up with the text "High in…" for the warning labels. So far, study methods have focused on either virtual stores or shopping simulations, and no studies have investigated in-store sales.…”
Section: Evidence For Warning Labels To Datementioning
confidence: 84%
“…The authors concluded that black octagons with the text "excess of... " had the strongest connection to perceived unhealthfulness. 17 This is similar to the final format of the labels implemented in Chile, with a slight difference in wording, which ended up with the text "High in…" for the warning labels.…”
Section: Evidence For Warning Labels To Datementioning
confidence: 84%
“…An increasingly large number of studies evaluating FOP nutrition labels' impact on awareness [13,14], acceptability [15], understanding [14,16,17], use [13], or effects in healthfulness perceptions [18,19], have been conducted among Latin American populations. However, limited literature exists evaluating FOP label effects on consumer purchasing intentions (e.g.…”
Section: Abstract: Nutritional Labeling Latin-america Shopping Timementioning
confidence: 99%
“…Esto sugiere que este tipo de EFP se entiende mejor una vez que se identifica y que, incluso, podría ser más efectivo si se presentara en colores más destacados. 29 En la vida real, más allá de la codificación por colores, un aspecto clave del mejor rendimiento del Nutri-Score observado en muchos estudios 9 puede estar relacionado con el uso de un indicador único que resume la calidad nutricional del alimento, en lugar de múltiples evaluaciones relacionadas con nutrientes. Los estudios anteriores han demostrado que los indicadores de resumen son más fáciles de entender por los consumidores, 19,20,30 en particular en las poblaciones vulnerables, las cuales son un objetivo importante en las políticas de nutrición de salud pública.…”
Section: Discussionunclassified